2013
DOI: 10.1111/ibi.12119
|View full text |Cite
|
Sign up to set email alerts
|

Divergent post‐breeding distribution and habitat associations of fledgling and adult Black‐footed AlbatrossesPhoebastria nigripesin theNorth Pacific

Abstract: Past tracking studies of marine animals have primarily targeted adults, biasing our understanding of at‐sea habitat use toward older life stages. Anthropogenic threats persist throughout the at‐sea ranges of all life stages and it is therefore of interest to population ecologists and managers alike to understand spatiotemporal distributions and possible niche differentiation between age‐classes. In albatrosses, particularly little is known about the juvenile life stage when fledglings depart the colonies and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 40 publications
1
32
1
Order By: Relevance
“…Unlike immature and adult short-tailed albatrosses, other studies examining post-fledgling distributions of other albatross species have identified relatively low overlap between immatures and adults (Weimerskirch et al 2006, Alderman et al 2010, Gutowsky et al 2014a. Initially, fledgling shorttailed albatrosses departed from their colonies with more varied and oceanic trajectories than previously tracked adults from Torishima who tended to follow the coast of Japan north to the Kuril Islands before either continuing along the continental margins or traveling offshore to make the crossing to the Aleutians (Suryan et al 2006).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Unlike immature and adult short-tailed albatrosses, other studies examining post-fledgling distributions of other albatross species have identified relatively low overlap between immatures and adults (Weimerskirch et al 2006, Alderman et al 2010, Gutowsky et al 2014a. Initially, fledgling shorttailed albatrosses departed from their colonies with more varied and oceanic trajectories than previously tracked adults from Torishima who tended to follow the coast of Japan north to the Kuril Islands before either continuing along the continental margins or traveling offshore to make the crossing to the Aleutians (Suryan et al 2006).…”
Section: Discussionmentioning
confidence: 98%
“…Segregation is even the case for shy albatrosses, where both adults and juveniles forage almost exclusively in Bass Strait and Southern Australian waters, yet show little overlap of core foraging areas (Alderman et al 2010). It is also the case for fledgling black-footed albatrosses (< 3 mo) who forage in subtropical waters, while adults prefer shelfbreak habitats in the North Pacific (Fischer et al 2009, Gutowsky et al 2014a). At present, competitive exclusion of preferred foraging areas by adult shorttailed albatrosses seems unlikely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seabirds are generally seasonally colonial and migratory, thus specific regions are more heavily visited during different periods of their annual cycle. Defining period-specific space use can help to identify the source or severity of common or distinct threats posed at different periods in the annual cycle for a species, and for further sub-groups divided by for example age-class (e.g., Péron and Grémillet, 2013;Riotte-Lambert and Weimerskirch, 2013;Gutowsky et al, 2014a), or sex (e.g., Phillips et al, 2004;Hedd et al, 2014). At the colony level, individual-based tracking data have been used to discern period-and colony-specific space use and potential associated impacts for population dynamics for a variety of seabird species (e.g., Young et al, 2009;Catry et al, 2011;Gaston et al, 2011;Wakefield et al, 2011;Frederiksen et al, 2012;McFarlane Tranquilla et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…During their first at-sea incursion, juveniles must go through their most critical stage (where mortality risk is higher) acquiring foraging skills over unknown areas (RiotteLambert and Weimerskirch, 2013). Despite the importance of this, juvenile dispersion in Procellariiformes is not well documented due to their high mortality and the difficulty on the recovery of devices because of their long periods at sea (Blanco and Quintana, 2014;Gutowsky et al, 2014). As far as we know, the at sea dispersion of this age class and its relationship with oceanographic features has been described in SGP and Northern Giant Petrel Macronectes halli through the study of ringed individuals (van den Hoff, 2011); and for the Wandering Albatross, Diomedea exulans, (Riotte-Lambert and Åkesson and Weimerskirch, 2014), the Scopoli's Shearwater, Calonectris diomedea, (P eron and Gr emillet, 2013), and the Black-footed Albatross, Phoebastria nigripes, (Gutowsky et al, 2014) through the use of satellite telemetry.…”
Section: Discussionmentioning
confidence: 99%